The Response Of Income Inequality To Monetary Policy Shock In Indonesia: A Vecm Approach - Adelia Dwi Rahmawati; Dafa Riandana Puta; Muhammad Rizieq Zamzani; Indra Suhendra; Cep Jandi Anwar (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Income inequality has so far proven to be one of the global economic problems which has become a topic of economic problems in almost all countries in the world, especially developing countries including Indonesia. This study aims to examine the influence that exists on inflation, exchange rates, interest rates, and money supply on the gini ratio in Indonesia in the period 1993 to 2022. The type of data used in this study is quantitative data and the data sources used were obtained from the Agency Center for Statistics (BPS) in 1993-2022. This study uses the Vector Error Correction Model (VECM) research test to analyze the existence of a long-term and short-term relationship between the independent variable and the dependent variable in time series data. The final results of the study show that the data used in this study are stationary after the first differentiation. From the VECM estimation, only interest rates were proven to have a significant long-term relationship with other variables, while no short-term relationship was found between the variables studied. The Engle Granger Causality test also shows that there is no significant causal relationship between the Gini Ratio and Interest Rates, Money Supply, Exchange Rates, and Inflation.